Condition assessment of façade rendering through in-situ testing - Inês Flores Colen (2008)
Condition assessment of rendering façades should compare required performance level with supplied performance level, on a practical and unambiguous basis, in order to help the serviceabilbity assessment and maintenance planning of rendering during the post-occupancy stage. The aaaplication of rendering on-site performance assessment has been difficult due to several reasons: design solutions are mostly prescriptive instead of based on performance assessment criteria; technical data provided by the manufacturers is insufficient or descriptive; and legal requirements (EN 998-1) are not enough to evaluate its global performance. Therefore, condition assessment have been restricted to visual inspections, without quantitative parameters through testing techniques.This paper presents a methodology that can be used in condition assessment (supplied in-service performance) of rendering façades through in-situ testing. This ongoing research (within the PhD study of the first author) intends to identify some rendering properties (related to surface condition, mechanical strength and water resistance) taht can be measured through on-site suitable and expedient techniques, and compared with standard hardened rendering properties or integrated into reference in-service performance profiles (IPP). Finally, performance criteria of mechanical strength is discussed through an experimental campaign that compares open porosity, apparent dry bulk density, compressive strength, adhesion strength, apparent ultrasonic pulse velocity and dynamic elastic modulus for different types of mainly cement-based renders (sound samples), used in common Portuguese buildings.KEYWORDS: Rendering, performance, in-situ, testing, condition assessment